URGENSI PERLUNYA PERUBAHAN PERSPEKTIF KEBIJAKAN UNTUK MENGOPTIMALKAN PERAN PEDAGANG HASIL - HASIL PERTANIAN DI KABUPATEN ENDE - Willybrordus Lanamana (AGRICA, 2008)
Research on changing the perspective of policy to optimize the role of traders of Agricultural products in Ende District has been carried out. The results of the study indicate that collective marketing institutional support at the farmer group level is needed to improve marketing access and efficiency. The underdevelopment of traditional markets is due to the lack of carrying capacities such as inadequate planning strategies and limited access to capital due to insufficient guarantees.